Neuroendocrine pathways underlying risk and resilience to PTSD in women - Ravi, Meghna (Front Neuroendocrinol, 2019)
Women are twice as likely than men to suffer from posttraumatic stress disorder (PTSD). While women have increased exposure to traumatic events of many types and have greater prevalence of comorbid psychiatric disorders compared to men, these differences do not account for the overall sex difference in the prevalence of PTSD. The current review summarizes significant findings that implicate the role of estradiol, progesterone, and allopregnanolone in female risk for PTSD symptoms and dysregulation of fear psychophysiology that is cardinal to PTSD. We also discuss how these steroid hormones influence the stress axis and neural substrates critical for the regulation of fear responses. Understanding the role of ovarian steroid hormones in risk and resilience for trauma-related adverse mental health outcomes across the lifespan in women has important translational, clinical, and intergenerational implications for mitigating the consequences of trauma exposure.